ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELEMAHAN PENGENDALIAN INTERN PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Daerah se Sumatera) - Fauza, Nailatul; -, Zulbahridar; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to examine the influence of economic growth, the size, local revenue and the complexity of the internal control weaknesses of local government. The dependent variable used in this study was the internal control weaknesses of local government and independent variables used in this study was economic growth, the size, local revenue and the complexity. This research use quantitative method against local government financial report in Sumatera which has been audited by BPK in 2012. The sample used in this research using purposive sampling method. The data is taken from 162 local government financial statements in Sumatera which has been audited by BPK in 2012 and selected based on criteria that has been determined, so that it is gotten 77 local government samples. The results of this research indicate that complexity have effect on the internal control weaknesses of local governmen. While the economic growth, the size and local revenue do not have effect on the internal control weaknesses of local government.Keywords: Internal Control Weakness, Economic Growth, Size, Local Revenue And Complexity.